Adiponectin, Leptin and Visfatin in Hypoxia and its Effect for Weight Loss in Obesity - Rausch, Linda K.; Hofer, Maximilian; Pramsohler, Stephan; Kaser, Susanne; Ebenbichler, Christoph; Haacke, Sven; Gatterer, Hannes; Netzer, Nikolaus C. (Frontiers in Endocrinology, 2018)
Rationale: Hypoxia induces leptin gene expression in human adipocytes via hypoxia-inducible factors (HIF-α/β). Under ambient moderate hypoxia, leptin in adipocytes is elevated for at least 14 days. Leptin is supposedly involved in the reduced food intake, increased utilization of fatty acids for energy production and possible weight loss observed at high altitudes. Literature on adiponectin and visfatin in high altitude is inconsistent with reports of elevated levels and non-elevated levels. Exercise in hypoxia studies in obese subjects have shown a significant weight loss after up to 3 weeks, but it is unclear if this effect holds up for longer time periods. Therefore, we aimed to investigate 32 obese subjects completing 52 exercise and rest sessions within 8 months at either moderate or sham hypoxia and to analyze leptin, adiponectin, and visfatin mRNA-expression at different time points of exposure. Methods: Abdominal subcutaneous fat biopsies were taken from 32 obese subjects before, after 3 months and after 8 months of intervention. Subjects were randomly divided into two groups and exercised at moderate intensity at two different study sites twice a week. The IG was exposed to normobaric hypoxia (FiO2: 14.0 ± 0.2%,) at exercise and at rest (FiO2: 12.0 ± 0.2%) and the CG to sham hypoxia. Quantitative real-time polymerase chain reaction (qPCR) was used in order to determine mRNA-levels of leptin, adiponectin, and visfatin. Results: No differences in leptin levels after 3 and 8 months compared to baseline and between groups were found. There was no significant difference regarding adiponectin or visfatin at any time point compared to baseline in the hypoxia group, but an increase after 3 months was seen in the control group at normoxia compared to the hypoxia group (adiponectin: p = 0.029 and visfatin: p = 0.014). Conclusion: In this first several months' duration randomized sham controlled hypoxia exercise and rest study with obese subjects, we found no time extended leptin mRNA-expression in subjects under hypoxia after 3 and 8 months compared to baseline levels. Moderate exercise in normoxia not in hypoxia leads to elevated adiponectin and visfatin levels after 3 months.